Nuclear Energy Policy Draft as an Alternative to Support National Resilience - Budiarti, Wahyu; Saragih, Herlina Juni; Yulivan, Ivan; Aritonang, Sovian (Journal of Public Representative and Society Provision, 2025)
This article analyses the nuclear energy policy model relevant to such countries as the United States of America, Russia, France and Japan. Moreover, this article also considers the international organizations, for example the International Atomic Energy Agency, as the supervising body in the field of nuclear energy programs and their security. The process of developing nuclear energy program must be well planned and must incorporate security, safety and environmental factors. Consequently, this nuclear energy policy must address all factors technical, economic, social-political and environmental factors underlying nuclear energy production.In this case, the IAEA and other international organizations contributing to stable and secure nuclear power usage are quite significant to the fulfillment of this requirement.great potential as an energy source that can reduce dependence on the use of fossil energy sources that are increasingly scarce and are often claimed to cause environmental damage. However, the use of nuclear energy also has risks that must be managed properly, such as nuclear accidents and the risk of terrorism. Several countries have developed their nuclear programs with the aim of meeting domestic energy needs and also as a national defense strategy. However, the development of this nuclear energy program also poses challenges in terms of security and safety. This article discusses the nuclear energy policy model that has been implemented in countries such as the United States, Russia, France, and Japan.